The impact of Duration of Untreated Psychosis on functioning and quality of life over one year of Coordinated Specialty Care (CSC). - Hadar Hazan; Sümeyra N Tayfur; Bin Zhou; Fangyong Li; Toni Gibbs-Dean; Sneha Karmani; Emily Kline; Maria Ferrara; Silvia Corbera; Sarah Riley; Laura A Yoviene Sykes; Cenk Tek; et al. (PLoS ONE)
Background This study examined the relationship between the Duration of Untreated Psychosis (DUP) and functional outcomes at baseline, 6 months, and 12 months after admission to Coordinated Specialty Care (CSC). Methods A total of 246 participants from two U.S. public-sector CSC programs were categorized into Low and High DUP groups using two criteria: (i) a median split of the DUP distribution and (ii) the World Health Organization (WHO) aspirational standard of 3 months. Changes in global functioning (GAF), social functioning (GF: Social), and occupational functioning (GF: Role), symptom severity (PANSS), and quality of life (QoL) were assessed using a Linear Mixed Model Repeated Measures (MMRM) analysis across the three time points. A Generalized Linear Model (GLM) with a logit link function was applied to analyze binary outcomes, specifically the status of being Neither in the Labor Force, Education, or Training (NLFET). Both models adjusted for time and site as covariates and used an unstructured variance-covariance matrix to account for within-subject correlations in repeated measures. The difference-in-differences method was employed to estimate the impact of DUP on outcomes over time, with results reported as least square means for continuous outcomes, odds ratios for binary outcomes, and 95% confidence intervals (CI) for both Low and High DUP groups. Results No significant differences were observed between the Low and High DUP groups at baseline. By 6 months, participants in the Low DUP group (DUP < 3 months) exhibited significantly greater improvements (reduction) in NLFET status (3-month OR = 3.25, p = 0.03; median split OR = 2.25, p = 0.03) and global functioning, GF: Role, and GF: Social. By 12 months, the Low DUP group continued to show significantly greater NLFET status improvement (3-month OR = 3.59, p = 0.03; median split OR = 3.40, p = 0.0032). Improvements in global functioning were sustained at 12 months, while social and occupational functioning gains were not. No significant differences were observed between groups for quality of life or symptom severity over time. Conclusion Shorter DUP is linked to more rapid functional recovery within the first year after CSC admission.